A prospective study of acute idiopathic neuropathy. III. Immunological studies. Issue 5 (May 1988) - Winer, J B; Gray, I A; Gregson, N A; Hughes, R A; Leibowitz, S; Shepherd, P; Taylor, W A; Yewdall, V
Abstract : The immune responses of 100 patients who presented with an acute idiopathic neuropathy were compared with those of age and sex matched controls. Blood lymphocytes and their subsets were counted with a fluorescent activated cell sorter. CD8+ (putative suppressor) lymphocytes were significantly reduced in the first week of the disease but total lymphocytes, total T and CD4+ (putative helper) cells were not altered. This reduction depended on the nature of the preceding infection. Serum complement C3 and C4 concentrations remained normal and immune complexes were rarely detected with a C1q binding assay. Complement-fixing antibodies to human peripheral nerve antigens were discovered in the serum of 7% of patients but only 1% of controls. Complement-fixing antibodies to galactocerebroside were not discovered in any sera. Enzyme-linked immunoassays detected increased antibody responses to galactocerebroside but none at all to human P2 myelin protein in the patient sera. Forty microliter of serum from five patients injected into the sciatic nerves of rats did not induce significantly more demyelination than the serum from control patients. It is concluded that auto-immune responses can only be detected by these techniques in a small minority of patients with acute idiopathic neuropathy.